1952
DOI: 10.1104/pp.27.2.417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypocotyl Temperature on Translocation of Carbohydrates from Bean Leaves

Abstract: In a recent paper, SWANSON and BOHNING (2) These studies have now been extended to include the influence of hypocotyl temperature on the rate of carbohydrate transport from bean leaves, using a similar technical approach.Seeds of Phaseolus vulgaris, variety Black Valentine, were planted in sand and allowed to germinate under greenhouse conditions. As soon as the hypocotyls had straightened, selected seedlings were transplanted to .a culture tray containing a complete culture solution. The plants were individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
7
1

Year Published

1952
1952
1967
1967

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
5
7
1
Order By: Relevance
“…Varying the temperature of the node has a direct effect on the transport of sugars in the phloem, and the results agree with the view that translocation is decreased by decreasing phloem temperature from about 25 "C (3,4,10,11,12,22,23,26,35). The temperature/translocation response and the derived Qlo values closely resemble those obtained from a wide variety of other physiological processes (2,15) and show no unusual deviations from which a clue concerning the mechanism might have been deduced.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Varying the temperature of the node has a direct effect on the transport of sugars in the phloem, and the results agree with the view that translocation is decreased by decreasing phloem temperature from about 25 "C (3,4,10,11,12,22,23,26,35). The temperature/translocation response and the derived Qlo values closely resemble those obtained from a wide variety of other physiological processes (2,15) and show no unusual deviations from which a clue concerning the mechanism might have been deduced.…”
Section: Discussionsupporting
confidence: 85%
“…This mechanism as proposed by Miinch (see ref. These conclusions were disputed on the basis of more direct experimental evidence supplied by Hewitt and Curtis (12) and by Swanson and his collaborators (3,4,22). Went and Hull reasoned that this was so since a lowered phloem temperature must have reduced its metabolic rate.…”
Section: Introductionmentioning
confidence: 99%
“…Below 50 translocation is reversibly inhibited and above 450 the process is irreversibly destroyed. The response of sugar movement to temperature change in Cucuirbita resembles that obtained for a number of other higher plant species (2,6,7,12,15,19) …”
supporting
confidence: 63%
“…Below 50 translocation is reversibly inhibited and above 450 the process is irreversibly destroyed. The response of sugar movement to temperature change in Cucuirbita resembles that obtained for a number of other higher plant species (2,6,7,12,15,19) and simulates the response to temperature change of a wide variety of other physiological processes (1,9 (2,7, 12, 15,19). There appears to be no need to asslume the existence of more than 1 mechanism conltrolling movement of the major part of the translocated sugar in any direction in Ciciirbita, as was considered necessary by Htull for the sugar beet (8) and by Hartt for the sugar cane (6).…”
mentioning
confidence: 54%
“…It is also of interest to note that this inhibition occurred even though the pod was outside of the direct line of transport to other areas of the plant. Böhning et al 7 found a similar "remote control" effect of cooling the hypocotyl of bean plants on movement of carbohydrate to the growing stem tip.…”
Section: The E//ect O/ Pod Temperature On the Distribution O/ Phosphomentioning
confidence: 90%